2014
DOI: 10.1093/jxb/eru474
|View full text |Cite
|
Sign up to set email alerts
|

qEMF3, a novel QTL for the early-morning flowering trait from wild rice, Oryza officinalis, to mitigate heat stress damage at flowering in rice, O. sativa

Abstract: Highlight qEMF3, a novel QTL for the early-morning flowering trait to mitigate heat-induced spikelet sterility at flowering in rice, was identified using a wild rice, Oryza officinalis, as a genetic resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
115
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 31 publications
1
115
1
Order By: Relevance
“…An nIL carrying qEMF3 was developed in the genetic background of nanjing 11 and then qEMF3 was transferred to the genetic background of IR64. nILs carrying qEMF3 had earlier FoT by 1.5-2.0 h than recurrent parents (Hirabayashi et al, 2015). It is remarkable that the EMF phenotype was observed in both temperate and tropical climates, and in two genetic backgrounds of Indica cultivars, whereas none of the popular cultivars in the tropics and subtropics had the EMF trait (Hirabayashi et al, 2015).…”
Section: Genetic Variation In Heat Tolerance To Wbcgmentioning
confidence: 93%
See 4 more Smart Citations
“…An nIL carrying qEMF3 was developed in the genetic background of nanjing 11 and then qEMF3 was transferred to the genetic background of IR64. nILs carrying qEMF3 had earlier FoT by 1.5-2.0 h than recurrent parents (Hirabayashi et al, 2015). It is remarkable that the EMF phenotype was observed in both temperate and tropical climates, and in two genetic backgrounds of Indica cultivars, whereas none of the popular cultivars in the tropics and subtropics had the EMF trait (Hirabayashi et al, 2015).…”
Section: Genetic Variation In Heat Tolerance To Wbcgmentioning
confidence: 93%
“…In fact, Hirabayashi et al (2015) revealed that the differences in peak FoT of 23 popular cultivars in the tropics and subtropics were only within 1.5 h. However, the wide variation in FoT among wild rice accessions is known (Sheehy et al, 2007). For example, some accessions of Oryza eichingeri and O. officinalis show early-morning flowering (EMF) phenotypes, an accession of O. australiensis shows late-afternoon flowering phenotype, and an accession of O. alta shows midnight flowering phenotype (Sheehy et al, 2007).…”
Section: Reports On the Actual Damage By Heat Stress On Spikelet Fertmentioning
confidence: 99%
See 3 more Smart Citations